Be care the risk of under fit in dose-response meta-analysis when using cubic spline - Xu, Chang; Zhang, Chao; Kwong, Joey S. W. (Annals of Translational Medicine; Vol 4, No 19 (October 15, 2016): Annals of Translational Medicine, 2016)
Dose-response meta-analysis (DMA) plays a vital role in investigating the potential causality between continuous variable and binary outcome. An increasing number of DMAs have been published during the past several years. In this letter, we aim to illustrate why some of them may at risk of under fit.